CHATBOT-BASED TOURIST GUIDE USING ARTIFICIAL INTELLIGENCE MARKUP LANGUAGE - ALI, ARAS AHMED; KAKA-KHAN, KANAAN MIKAEL; AL-CHALABI, ISRAA (Journal of Duhok University, 2023)
The tourism industry heavily relies on effective communication, guidance, and assistance to ensure a positive experience for travelers. With the advent of technology, chatbots have emerged as a popular solution for providing aid and direction to tourists. This research paper presents a comprehensive exploration of the design and implementation of a cutting-edge chatbot tailored for tourist guidance, leveraging the power of Artificial Intelligence Markup Language (AIML). The case study focuses on Sulaimani City, wherein a robust dataset comprising 352 meticulously crafted questions and corresponding answers was curated. The developed chatbot model was then seamlessly integrated and deployed on a dedicated test website, enabling real users to interact and engage with it. To gauge the efficacy of the model, a multifaceted evaluation encompassing user satisfaction, accuracy, and response type was conducted. The results unequivocally demonstrate that the AIML-based chatbot surpassed the performance of traditional web-based tourist guides, achieving higher levels of user satisfaction. However, one notable limitation of this research is the use of a small-scale dataset, potentially affecting the chatbot’s real-world performance and generalizability. This pioneering research underscores the immense potential of chatbot technology as an indispensable tool for delivering comprehensive and reliable tourist information, thereby revolutionizing the tourism industry.